Mental health trajectories among women in Australia as they age. (3rd July 2019) - Tran, Thach; Hammarberg, Karin; Ryan, Joanne; Lowthian, Judy; Freak-Poli, Rosanne; Owen, Alice; Kirkman, Maggie; Curtis, Andrea; Rowe, Heather; Brown, Helen; Ward, Stephanie; Britt, Carlene; et al.
ABSTRACT: Objectives: To ascertain the trajectories of mental health among women in Australia assessed in repeat waves from their early 70 s to the end of their lives or their mid 80 s. Method: Secondary analysis of data contributed by the 1921–26 cohort of the Australian Longitudinal Study of Women's Health Waves 1–6. Primary outcome was the 4-item SF-36 Vitality Subscale, which assesses mental health as life satisfaction, social participation, energy and enthusiasm. Structural, individual and intermediary factors were assessed using study-specific and standardised measures. Trajectories were identified using Growth Mixture Modelling and associations with baseline characteristics with Structural Equation Modelling. Results: 12, 432 women completed Survey One. Three mental health trajectories: stable high (77%); stable low (18.2%) and declining from high to low (4.8%) were identified. Compared to the stable high group, women in the stable low group were significantly less physically active, had more nutritional risks, more recent adverse life events, fewer social interactions and less social support, reported more stress and were more likely to have a serious illness or disability at Survey One. The declining group had similar characteristics to the stable high group, but were significantly more likely to report at baseline that they had experienced recent financial, physical and emotional elder abuse. These interact, but not directly with socioeconomic position and marital status. Conclusion: Mental health among older women is related to social relationships, general health, access to physical activity and healthy nutrition, coincidental adverse life events and experiences of interpersonal violence, in particular elder abuse.